Identification and Assessment of Resistance to Fusarium Head Blight and Mycotoxin Accumulation Among 99 Wheat Varieties - Chen Huang; Dezhou Cui; Yongbo Li; Yamei Zhuang; Xinxia Sui; Qingqi Fan (Agronomy, 2025)
Fusarium head blight (FHB) is a major devastating wheat fungal disease. Mycotoxins act as virulent factor for FHB progression, including deoxynivalenol (DON), 15-acetyl deoxynivalenol (15-ADON), 3-acetyl deoxynivalenol (3-ADON), deoxynivalenol-3-glucoside (D3G), and zearalenone (ZEN). To identify resistant germplasm against FHB and mycotoxin accumulation, we evaluated 99 wheat cultivars for FHB severity using point inoculation by three FHB isolates under greenhouse and field conditions. FHB severity of selected varieties evaluated in the fields were correlated with that in greenhouse (p < 0.01). Inoculated spikes from 20 varieties were examined for mycotoxin accumulation, employing an LC-MS/MS method that differentiated five mycotoxins. Five cultivars exhibited resistance to both FHB and mycotoxin accumulation, with FHB severity averaging from 13.36% to 33.37%, and DON accumulation below 2400.0 µg/kg, across various conditions. Seven dominant varieties exhibited moderate resistance to FHB and mycotoxin accumulation. FHB severity was significantly positively correlated with DON accumulation, but negatively correlated to the D3G to DON ratio, across distinct groups of FHB resistance (p < 0.01) after inoculation of three distinct isolates, although no correlation was observed within-group. In the present study, Shannong20, Huaimai20, and Sunlin were identified with resistance to both FHB and mycotoxins with superior agronomic performance, providing promising materials for improving disease resistance in breeding programs.